Novel origami-inspired metamaterials: Design, mechanical testing and finite element modelling - Wickeler, Anastasia L.; Naguib, Hani E. (Materials & design, 2020)
Two novel, origami-inspired, metamaterials were designed, mechanically tested, and modelled. One novel origami model was folded using a triangular based crease pattern and the other was folded using a rectangular based crease pattern. The origami-inspired metamaterial sheets were fabricated from polylactic acid using fused deposition additive manufacturing. Several configurations, parameterized by varying the fold angle, were mechanically tested under compression and impact loads. It was found that the specific elastic compression modulus of these novel designs was higher, ranging from 594 MPa/kg to 926 MPa/kg, than existing origami-inspired structures made based on the popular Ron-Resch design, which had specific elastic compression moduli between 15 MPa/kg to 365 MPa/kg. A finite element model further analysed the stress distribution of the core structures under compression loads. The impact testing results showed that the pattern of the tessellated cores affected the amount of impact force transferred through the samples, whereas the fold angle of the origami-inspired design had little impact on the results. The rectangular structure was shown to transfer approximately 50–75% of the force transferred by the triangular structure under impact loads. [Display omitted] •Two novel, origami-inspired, tessellated patterns were designed for use as light-weight cores in sandwich structures.•Compressions tests showed that increasing fold angle improved the metamaterials’ resistance to compression loads.•The elastic compression moduli of both new designs were higher than that of existing Miura-ori and Ron Resch designs.•The ability to absorb impact force was dependant on the tessellated design pattern and independent of the origami fold angle.